(untitled) (Global Journal of Medical Research, 2020)
Health care professionals exercise professional power which is set by their training, education, skills, regulation etc. ’Professions’ are seen as a source of power (by the use of knowledge, skills and expertise) in professional power perspectives of theory of professions, which is mainly focuses on control over professions, dominance, autonomy and professional relationships. In this perspective, health care professionals gain such professional power from knowledge, training, education and form their interprofessional team and organisations, and professional power has a great influence in determining professional behaviour and dominance. As a result of advancement in therapeutic technologies, emergence of new specialities in health care and managerial control, power dynamics between health care professionals are changing. Relative power between health care professionals is evident and health care professionals complement to each other for flawless health services and learning from each other.